Determinant of interaction between Filipino elderly siblings living in an urban poor community - Feliciano, Riana Marie de Luna
Old age is the time where siblings may or may not maintain interaction with each other due to many factors. Determinants of their interaction, whether these facilitate or hinder interaction must be studied to help the elderly maintain interaction with their siblings. Using purposive and snowballing sampling techniques, 30 elderly living in Sitio Veterans, Barangay Bagong Silangan, Quezon City were interviewed. A demographic questionnaire to elicit the basic information of the respondents and an interviewed schedule to gather the information needed from the elderly were constructed for this research. The respondents were interviewed to know if they still maintain interaction with their siblings, to determine what the factors associated with their interaction are, and to identify which determinants facilitate and which hinder interaction between the Filipino elderly siblings. Results showed the Filipino elderly still maintain interaction with their siblings. Found to be determinants of interaction were gender, financial status marital status, parent status and number of children, feelings towards siblings, proximity of residence, and loss of contact information. Those that facilitate were gender and positive feelings toward siblings while those that hinder were negative health and financial status and loss of contact information. Other determinants such as parent status and number of children, marital status, and the proximity of residences were found to either facilitate or hinder interaction depending on the situation of the elderly. This study highlighted the importance of continuing family ties over time and thus encouraging the family members, the caregivers, and the policy and program planners to maintain or improve communication between the siblings.